Trade union merger strategies : purpose, process, and performance - Undy, R. [ (Roger)] (Oxford, England ; New York : Oxford University Press, 2008)
As Trades Union membership has declined, merger and amalgamation have been prominent features in strategies of revitalization. Yet, there is very little systematic, empirical research into their effects on unions or the wider union movement. This study fills this gap with an analysis of British union mergers since 1978.
1. Nature and purpose of the study -- 2. Union strategies in context -- 3. Transfer strategies -- 4. Transfer negotiations -- 5. Transfers: post-merger performance -- 6. Amalgamation strategies -- 7. Amalgamation negotiations -- 8. Amalgamations: post-merger performance -- 9. Mergers: good or bad for unions
Includes bibliographical references (p. [273]-279) and index
Keywords: Labor unions -- Mergers -- Great Britain; Labor unions -- Great Britain -- History -- 20th century